Pelanggaran Hak Asasi Manusia terhadap Pekerja Pabrik Garmen H&M di Kamboja - Sakti, Ai Clara; Windiani, Reni (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
The Cambodian government has set regulations regarding the human rights of factory workers, especially in the garment sector, based on ILO conventions. H&M is a multinational company that has a garment industry supplier in Cambodia. The problem here is that there is often the practice of human rights violations in the form of forced labor inside the H&M factories in Cambodia. Although there are already regulations related to the human rights for workers from the Cambodian government and also the ILO, even H&M has also established a code of conduct that must be obeyed by all suppliers in all country, however, violations of regulations are still common. Then, this research has a focus in finding the reasons why H&M still violates workers’ rights. In answering this question, this research uses neoliberal economic theory, using the concept of MNC, and dependence. This study uses explanatory methods in answering problems. The results of this study found that this violation occurred due to the purpose of H&M which is to increase the maximum profit. Then, even though there are rules from the ILO, a multinational company is not obliged to comply with these rules. Another reason is that law enforcement that regulates the rights of workers has not been done maximally.